Species Specific Detection of Methicillin-resistant Staphylococcus aureus (MRSA) by Multiplex PCR - Mehdi Haseli; Ali Ramazani; Alireza Khaleghi Khorram; Laleh Mehrad (مجله دانشکده پزشکی اصفهان, 2013)
Introduction: Staphylococcus aureus is one of the pathogens that is a major agent of infectious diseases. So detection, control and treatment of this pathogen is very important. The objective of this study is setting up a fast method to detect methicillin resistant Staphylococcus aureus (MRSA) for better management of diseases related to this pathogen.